Prudent Management of the Mid-Cheek Mass: Revisiting the Accessory Parotid Gland Tumor - Alassaf, Arige (Latakia University Journal -Medical Sciences Series, 2018)
Objective:A mass arising in the mid-cheek region may often be overlooked as a rare accessory lobe parotid neoplasm> this report serves to revisit the topic of accessory parotid gland neoplasms to emphasize proper management, particularly the surgical aspects, so that consequences of salivary fistula, facial nerve paralysis, and recurrence are avoided. Methods: this is a retrospective review of four accessory parotid gland neoplasms and five other masses mimicking this lesion. Results: over a 6 year period, we have encountered four true accessory lobe tumors, all pleomorphic adenomas. All were removed through a wide parotidectomy-style approach modified by extending incisions anterosuperiorly and inferoanteriorly. The only complication was a minor salivary fistula in one patient. There were no permanent facial paralyses. Conclusions: accessory parotid gland neoplasms are rare and may present as innocuous extraparotid mid-cheek masses. A high index of suspicion, prudent diagnostic skills, including (FNA) followed by computed tomography (CT), and meticulous surgical approach (extended parotidectomy-style incision and limited peripheral nerve dissection when possible) are the keys to successful management of these lesions. التدبير الصحيح لكتلة في القسم المتوسط للوجه: إعادة النظر في ورم الفص الإضافي (الملحق) للغدة النكفية الموضوع:يمكن لكتلة ناشئة في القسم المتوسط من الخد أن يحدث خطأ في تشخيصها ككتلة على حساب الفصّ الملحق (الإضافي) للغدة النكفية، وذلك بسبب ندرة هذه الحالة. تهدف هذه الدراسة إلى إعادة وضع نقاط علّام لتموضع ورم الفص الملحق للغدة النكفية، بهدف تدبيره بشكل صحيح وتجنب تشكل النواسير اللعابية وشلل العصب الوجهي والنكس الورمي. الطرق: دراسة راجعة شملت أربع كتل ناشئة على حساب فص النكفة الملحق، ومقارنتها بخمس حالات مماثلة لكتل ناشئة في القسم المتوسط للخد. النتائج: خلال مدة الدراسة (ست سنوات) تم تشخيص أربع حالات لورم ناشئ على حساب فص النكفة الملحق، جميعها كانت ورماً غدياً مختلطاً، تم استئصالها جراحياً بمدخل جراحة النكفة التقليدي مع تمديد الشق الجراحي نحو الأعلى والأمام ونحو الأسفل والأمام. الاختلاط الوحيد الذي تطور هو ناسور لعابي صغير عند مريض واحد، ولم تحدث أية حالة لشلل عصب وجهي دائم. الخلاصة: أورام فص النكفة الملحق نادرة جداً ويمكن أن تشبه ورماً خبيثاً خارج النكفة. يعد كلّ من التشخيص اعتماداً على الاشتباه، والخبرة التشخيصية الماهرة، وعلى خزعة الخلايا بالإبرة (FNA)، وعلى التصوير الطبقي المحوري، وتطبيق المدخل المعتمَد لجراحة النكفة مع توسيعه وتقليل التسليخ على العصب الوجهي في المحيط قدر الإمكان، عوامل هامة للتدبير الجيد لتلك الآفات.